2021
DOI: 10.3390/scipharm89020024
|View full text |Cite
|
Sign up to set email alerts
|

Zolmitriptan Intranasal Spanlastics for Enhanced Migraine Treatment; Formulation Parameters Optimized via Quality by Design Approach

Abstract: Zolmitriptan is a potent second-generation triptan prescribed for migraine attacks. It suffers low bioavailability (40%) after oral administration due to the hepatic first-pass metabolism. Spanlastics are surfactant-based elastic vesicular drug carrier systems. This study aimed to design and optimize intranasal spanlastic formulations as an alternative approach that directly targets brain delivery, enhancing its bioavailability and avoiding the first-pass effect. The quality by design approach was applied to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Zeta potential values were evaluated by using the same equipment in a single-use capillary zeta cell at 25 • C and dissolved in deionized water. The particle size and ZP values given are the averages of 3 measurements [45,46].…”
Section: Characterization Of Developed Nano-formulations (Particle Si...mentioning
confidence: 99%
“…Zeta potential values were evaluated by using the same equipment in a single-use capillary zeta cell at 25 • C and dissolved in deionized water. The particle size and ZP values given are the averages of 3 measurements [45,46].…”
Section: Characterization Of Developed Nano-formulations (Particle Si...mentioning
confidence: 99%
“…A key consideration in formulating Spanlastics materials is selecting the appropriate EA that provides the necessary elasticity and deformability to navigate the tight connections of relatively impermeable membranes ( Saleh et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that spanlastics can deliver specific drugs to the brain through nose-to-brain delivery. For example, Saleh et al observed the “increased drug penetration across the nasal membrane in zolmitriptan-loaded spanlastic formulations, confirming the promising impact of intra-nasal dosing for brain delivery” [ 26 ]. Furthermore, Rehab et al observed that “the formation of granisetron hydrochloride spanlastic gel appears to promote the brain bioavailability of the carried drug, providing a higher level of treatment in the brain” [ 27 ].…”
Section: Introductionmentioning
confidence: 99%